s. o. s. Eradication of rights, stories and narratives around drugs. : Presentation of the dossier “Drug in Iberoamerica: regulation, demands and consumptions” - Rodríguez Mera, Andrés (2023)
The regulation of psychoactive substances continues to be a topic of debate: some countries decriminalize drug possession and use, while others maintain the death penalty for drug-related offenses. The sale of illegal substances often involves labor conflicts and a lack of investment alternatives in the legal economy. In Latin America, drug policies are often ineffective and problematic, and even dissimilar in each of the countries, for example, in the case of Bolivia, responsible and functional consumption is advocated, while in Ecuador prohibitionism is incongruent with the reality of those who consume and sell cannabis. This dossier offers different perspectives on the regulation, demand and consumption of psychoactive substances in Ibero-America.